2008
DOI: 10.3346/jkms.2008.23.2.218
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Response Relationship between Types of Physical Activity and Distress

Abstract: This study aimed to examine whether a dose-response relationship exists between psychological distress and types of physical activity (total, occupational, and leisuretime). The study subjects (233 men and 313 women) were recruited for a study on cardiovascular disease in the Yangpyeong community located in South Korea. The type and characteristics of physical activity were measured with a modified version of the Stanford 5 city project's questionnaire by well-trained interviewers using a standard protocol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Similar findings were reported in a recent study whereby young Australian women showed positive associations between depression and occupational PA as measured by the IPAQ (McKercher et al, 2009). Also, analogously to our study, vigorous occupational PA was found to be negatively associated with mental well-being in male adults (Kim et al, 2008).…”
Section: Occupational Pasupporting
confidence: 90%
See 2 more Smart Citations
“…Similar findings were reported in a recent study whereby young Australian women showed positive associations between depression and occupational PA as measured by the IPAQ (McKercher et al, 2009). Also, analogously to our study, vigorous occupational PA was found to be negatively associated with mental well-being in male adults (Kim et al, 2008).…”
Section: Occupational Pasupporting
confidence: 90%
“…Several studies have reported associations between PA and mental well-being, stratified by gender (e.g., Bernaards et al, 2006;Kim et al, 2008;Strö hle et al, 2007;Wendel-Vos et al, 2004). These findings are mixed and inconclusive, with some studies reporting no gender differences (e.g., Bernaards et al, 2006;Stubbe, de Moor, Boomsma, & de Geus, 2007) or only minimal gender differences (e.g., Tessier et al, 2007), and others finding stronger associations in men (e.g., Bü ltmann et al, 2002;Kim et al, 2008) or in women (Tessier et al, 2007). Given these inconsistent findings, it is important to continue exploring the moderating effects of gender, particularly in relation to PA domains other than leisure-time (household, occupational, and transport) which have not been well-studied.…”
Section: Physical Activity and Mental Well-being: Socio-demographic Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a dose-response relationship has been observed in studies with different measurements of effect (Haennel and Lemire, 2002;Kim et al, 2008;Lee and Skerrett, 2001;Lollgen et al, 2009;Martin et al, 2009;Mayer-Davis et al, 1998;Ohkawara et al, 2007;Thune and Furberg, 2001), there is still a controversy about whether or not this relationship is linear. On one hand, an inverse linear relationship has been seen between the amount of physical activity and all-cause death (Lee and Skerrett, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Various studies have reported a dose-response relationship between total physical activity and a lower risk of all-cause mortality (Lee and Skerrett, 2001;Lollgen et al, 2009), cardiovascular disease (Haennel and Lemire, 2002), cancer (Thune and Furberg, 2001), type 2 diabetes mellitus (Mayer-Davis et al, 1998), adiposity (Ohkawara et al, 2007), as well as better mental health (Kim et al, 2008) and quality of life (Martin et al, 2009).…”
Section: Introductionmentioning
confidence: 97%